2014
DOI: 10.12948/issn14531305/18.1.2014.07
|View full text |Cite
|
Sign up to set email alerts
|

Extending and Refining Usability Heuristics to Better Address User Centered Design Issues in the Development and Evaluation of Municipal Websites

Abstract: Usability of public administration websites is a key issue in the information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Usability and user interface quality are the major factors recognized in literature for software to succeed (Bakaev, & Avdeenko, 2013;Bhattacharya, & Laha, 2013;Caine et al, 2015;Chu, & Tanaka, 2015;Pribeanu, 2014). In addition, about 50% of all program code produced when information systems applications are built is devoted to user interface quality design (Bakaev, & Avdeenko, 2013).…”
Section: Relevance Of Pictorial Images and Voice Prompts Interface Dementioning
confidence: 99%
“…Usability and user interface quality are the major factors recognized in literature for software to succeed (Bakaev, & Avdeenko, 2013;Bhattacharya, & Laha, 2013;Caine et al, 2015;Chu, & Tanaka, 2015;Pribeanu, 2014). In addition, about 50% of all program code produced when information systems applications are built is devoted to user interface quality design (Bakaev, & Avdeenko, 2013).…”
Section: Relevance Of Pictorial Images and Voice Prompts Interface Dementioning
confidence: 99%
“…The usability evaluation has been carried out in a scenario-based approach and revealed some difficulties when using the usability heuristics to explain and document specific problems for municipal websites. Therefore, the set has been refined by merging two existing heuristics and adding two new heuristics, which resulted in a total of 25 heuristics [18]. However, our further experience with other kinds of web applications suggested that several changes are needed.…”
Section: The Revised Usability Heuristics Reasons For Changementioning
confidence: 99%
“…In a previous work, a set of 24 heuristics has been proposed that have been used in the evaluation of municipal websites. Based on the evaluation results, the heuristics have been further refined [18]. A task-based inspection method has been used: all evaluators are testing the interface with the same tasks and the severity of the evaluation problems is related to the task goal.…”
Section: Introductionmentioning
confidence: 99%
“…Ease of use is one of the tools to measure and evaluate MAR apps [29]. Usability has been applied in [30], [31], [25], [24], [32] and [33] where usability stimulates users' satisfaction and engagement with the MAR app.…”
Section: Usabilitymentioning
confidence: 99%
“…It fosters informal learning where learning takes place through searching and exploring. Curiosity has been applied in studies by [40], [39], [31], and [36] which indicated that apps that boost users' interest can successfully engage users in a learning environment.…”
Section: Curiositymentioning
confidence: 99%